Should Empathic Development Be a Priority in Biomedical Ethics Teaching? A Critical Perspective - Maxwell, Bruce (Cambridge quarterly of healthcare ethics, 2010)
Biomedical ethics is an essential part of the medical curriculum because it is thought to enrich moral reflection and conduce to ethical decisionmaking and ethical behavior. In recent years, however, the received idea that competency in moral reasoning leads to moral responsibility “in the field” has been the subject of sustained attention. Today, moral education and development research widely recognize moral reasoning as being but one among at least four distinguishable dimensions of psychological moral functioning alongside moral motivation, moral character, and moral sensitivity. In a reflection of this framework, medical educators and curriculum planners repeatedly advance the idea that educators should be concerned with supporting empathy, and this, very often, as a means of improving on and broadening medical ethics education’s traditional focus on moral reasoning.